2019
DOI: 10.1016/j.nbd.2019.104522
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for Parkinson's disease modulates high-frequency evoked and spontaneous neural activity

Abstract: Deep brain stimulation is an established therapy for Parkinson's disease; however, its effectiveness is hindered by limited understanding of therapeutic mechanisms and the lack of a robust feedback signal for tailoring stimulation. We recently reported that subthalamic nucleus deep brain stimulation evokes a neural response resembling a decaying high-frequency (200-500 Hz) oscillation that typically has a duration of at least 10 ms and is localizable to the dorsal sub-region. As the morphology of this response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 55 publications
5
82
0
Order By: Relevance
“…It is important to note that a contradictory hypothesis was suggested by Sinclair et al 44 , since the authors report a decrease in HFO frequency after high-frequency DBS. The authors suggested that DBS and dopaminergic therapy have different mechanisms of action.…”
Section: Dbsmentioning
confidence: 91%
“…It is important to note that a contradictory hypothesis was suggested by Sinclair et al 44 , since the authors report a decrease in HFO frequency after high-frequency DBS. The authors suggested that DBS and dopaminergic therapy have different mechanisms of action.…”
Section: Dbsmentioning
confidence: 91%
“…These findings raise the possibility that the ERNA amplitude could help guide electrode contact selection. Moreover, the frequency of ERNA modulates during DBS (Supplementary Figure S4E), reducing on average from around 310 Hz pre-therapy to around 260 Hz when therapy reaches clinically effective levels (Sinclair et al, 2019). It is intriguing that the latter value is around twice the commonly employed applied STN DBS frequency of 130 Hz, though it is crucial to note that the plateau frequency that ERNA reaches with therapeutic DBS differs between individuals.…”
Section: Dbs Local Evoked Potentials: the Ernamentioning
confidence: 97%
“…However, these oscillations are small (<15 µV), and can be difficult to detect in and across certain conditions. In this light, we propose a new biomarker, evoked resonant neural activity (ERNA), which is significantly larger than the beta band (>100 µV) and can be reliably recorded across all conditions (Sinclair et al, 2018(Sinclair et al, , 2019. ERNA is evoked and recorded from within the STN itself and is generated by a train of square biphasic pulses.…”
Section: Dbs Local Evoked Potentials: the Ernamentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of these signals is that they use methods of synchronous detection to avoid artifacts. Similar to chopper methods to remove low-frequency offset and drift [25], if the stimulation frequency is above the cardiac energy, then the impact of the cardiac artifact is greatly attenuated. The major trade-off of this technique is the bandwidth required for sampling, typically ten times higher than for low frequency field potentials, and the need to manage stimulation artifacts to allow for resolution of physiological signals within milliseconds of stimulation termination [24], [26].…”
Section: Model Interpretationmentioning
confidence: 99%